Comparison of some anatomical, chemical and fibrous characteristics of Turkish Pine (Pinus Brutia Ten.) sampled from different regions - Abuamoud, Mabrouka Mohamed Muftah; Ateş, Saim; Durmaz, Ekrem (Kastamonu University, 2018)
Aim of study: In this study, it was aimed to research the anatomical properties, chemical composition of the cell wall and fiber characteristics of Turkish Pine (Pinus brutia Ten.) wood sampled from five different zone of Kastamonu province in Turkey.   Area of study: This study was performed at the laboratories of Department of Forest Industry Engineering and Department of Biology, Kastamonu University. Material and Methods: Turkish Pine (Pinus brutia Ten.) wood samples obtained from five different zone of Kastamonu (Hanönü, Bozkurt, Araç, İnebolu and Tosya) were used as experimental materials. Anatomical properties (ray number, tracheid widths, widths of early and late wood zones), wood chemical components (ethanol extraction (%), lignin (%), holocellulose (%), alpha cellulose (%), 1% NaOH solubility (%), cold water solubility (%), hot water solubility (%) and ash specification (%)) and fibrous characteristics of wood fibers (fiber length, fiber width, lumen width and cell wall thickness) were measured according to standard methods.Main results: This study indicated that the samples obtained from Tosya have maximum fibre length with 3.15 mm and maximum lumen width with 27.75 mm, whereas maximum fibre width was found in samples obtained from İnebolu with 42.27 mm and maximum cell wall thickness was seen in samples of İnebolu with 7.90 mm. As a consequence of chemical analyses, it was confirmed that holocellulose ratio, alpha-cellulose ratio, lignin ratio, 1% NaOH solubility, ethanol solubility, hot water solubility, cold water solubility and ash ratio changed within the range of 70.37%-72.38%, 42.62%-47.30%, 26.04%-27.86%, 12.38%-13.14%, 2.38%-3.41%, 2.86%-3.83%, 2.29%-3.27% and 0.26%-0.40%, respectively. When it was looked to the results of anatomical research, it was determined that the samples taken from Hanönü had maximum average ray numbers with 7. Likewise, maximum tracheid widths were found samples in İnebolu and Bozkurt with 1.31 µm. Besides, maximum earlywood width was confirmed samples taken from Bozkurt with 0.47 mm, whereas maximum latewood width was confirmed samples taken from Hanönü with 1.31 mm. Research highlights: It is inferred that the same tree species taken from different areas have varied anatomical, chemical and fibre properties measured by means of this study. Because of this, it can be stated that growth location properties and growth media affect the characteristics of same type trees.
Keywords: Turkish Pine; Anatomical Properties; Wood Chemical Components; Wood Fibre Characteristics; Kızılçam; Anatomik Özellikler; Odun Kimyasal Bileşenleri; Odun Lif Özellikleri; 15. Life on land